WHY DO GAMERS PURCHASE VIRTUAL ITEMS IN MOBA GAMES? - Tuzzahra, Andini Ginanti; Edastama, Primasatria (Fakultas Ekonomi dan Bisnis, UNTAN, 2023)
This study explores and analyzes multiplayer online battle arena (MOBA) gamers